Multisensory fashion communication media towards impression management. (2015) - Choi, Yongsoon; Cheok, Adrian David
This paper shows the design of two fashion accessories, sound perfume and light perfume that we created to see whether multisensory stimulations can manage users impressions formed about themselves by their partner during face-to-face conversations. Each system targets a different function of impression management. Sound perfume uses auditory and olfactory stimulations along with the eye contact interaction technique to focus on the presentational aspect of impression management. Light perfume uses visual and olfactory stimulations along with the mirroring interaction technique for the affect function of impression management. We also show the results of a preliminary study to test whether the systems worked as designed.